Modulation of Immune Responses by Particle Size and Shape - Baranov, Maksim V.; Kumar, Manoj; Sacanna, Stefano; Thutupalli, Shashi; van den Bogaart, Geert (Frontiers in Immunology, 2021)
The immune system has to cope with a wide range of irregularly-shaped pathogens that can actively move (e.g., by flagella) and also dynamically remodel their shape (e.g., transition from yeast-shaped to hyphal fungi). The goal of this review is to draw general conclusions of how the size and geometry of a pathogen affect its uptake and processing by phagocytes of the immune system. We compared both theoretical and experimental studies with different cells, model particles and pathogenic microbes (particularly fungi) showing that particle size, shape, rigidity and surface roughness are important parameters for cellular uptake and subsequent immune responses, particularly inflammasome activation and T cell activation. Understanding how the physical properties of particles affect immune responses can aid the design of better vaccines.